Complete data from a mycotoxin survey conducted in western Honduras in 2017 and 2018 - Sabillón, Luis; Alvarado, Jackeline; Leiva, Alejandra; Mendoza, Rodrigo; Espinal, Raúl; Leslie, John F.; Bianchini, Andréia (My University, 2022)
· We determined the occurrence of and exposure levels to aflatoxins and fumonisins in maize intended for human and animal consumption in food-insecure regions of western Honduras by using a monoclonal antibody-based affinity spectrofluorimetric method. · Fumonisins were detected in 614/631 samples of maize destined for human consumption at 0.3 to 41 mg/Kg. Of the 614 positive samples, 147 had fumonisin levels exceeding the U.S. FDA advisory threshold of 4.0 mg/Kg. · Aflatoxins were detected in 109 of the 631 samples with concentrations between 1.0 and 490 µg/Kg. Aflatoxin levels in 34 samples exceeded the FDA regulatory limit of 20 µg/Kg. · Aflatoxins and fumonisins co-occurred in 106/631 samples with 60 samples containing both toxins at levels greater than the FDA regulatory levels. · Samples of maize intended for animal feed had significantly higher aflatoxin and fumonisin contamination levels than those observed in samples destined for human consumption.
Keywords: Aflatoxin; Fumonisin; Maize; Public health; Animal feed; Subsistence farmers